Modeling and simulation for three-phase three-wire active filter - Bùi Đông Hải; Trần Thu Hà; Võ Hoàng Lan Khuê (Journal of Technical Education Science, 2018)
With the development of modern industry, a various nonlinear and time-varying electronic devices such as inverters, rectifiers, and switching power supplies are widely utilized. These solid-state converters inject harmonics into the power lines and result in serious distortion in the supply current and voltage and decrease the power quality. Harmonics increase the conduction losses, eddy current losses and also have bad impacts on other loads connected to the same voltage source. This article presents a three-phase three-wire shunt active filter configuration. The proposed scheme implements simplified control algorithms depending on the direct current control (DCC) techniques for designing trajectories in sliding mode control based shunt active power filter (SAPF). The performances of the AF were verified through a simulation with MATLAB-SIMULINK. The THD of source current is reduced from 26,80% to 2,30%. The results indicate that proposed active filter can reduce the current harmonics